Road pavement longitudinal evenness quantification as stationary stochastic process - Leitner, Bohuš; Decký, Martin; Kováč, Matúš (Transport, 2019)
One of the requirements concerning pavement quality is the evenness of its surface. Pavement unevenness has a random character and has an adverse influence to rolling resistance, tyre–pavement coherence, safety and the driving comfort. Knowledge of “longitudinal unevenness” has been long recognized as an important criteria of road performance, not only for safety by causing vehicle vibrations and affecting ride comfort but also as a major factor in pavement deterioration and working conditions of vehicles. The paper presents two original devices for the measurement of pavement longitudinal unevenness designed as a reaction to results and experiences gathered from a few years’ research activities, measurements and evaluations of road pavement evenness carried out in the authors' work place (University of Žilina – UNIZA). The first equipment has been designed as a single-wheel trailing vehicle and has been constructed on the Double-mass Measuring Set (DMS) principle and it is referred to as UNIZA single-wheel vehicle JP VSDS. The main reason for designing the device were authors’ findings that the reference quarter car model (used for calculation of International Roughness Index – IRI) can provide evaluation, which can be in contradiction with ride safety. This fact is determined by overvaluation of the short wavelengths and undervaluation the longer wavelengths by reference model. The second one is a profiler with very high resolution of surface scanning using mathematical models for unevenness evaluation. The device is referred to as Dynamic Road Scanner (DRS). The reason for designing of this equipment was in the first place insufficient repeatability of transversal unevenness measurements of device used by Slovak Road Administration, but for the purpose of correctness and measurements accuracy verifying were also results of longitudinal unevenness measurements compared. The paper presents results of evaluation by international established dynamic quantifiers of longitudinal unevenness based on measurements performed by these devices on three selected road sections in Slovakia. In the next part of the paper are compared IRI values obtained by mathematical calculations using reference quarter car model “driving” on road section profile measured by geodetic survey with IRI values obtained by conversion of the unevenness degree C (measured by UNIZA single-wheel vehicle JP VSDS) and IRI values measured by profilometer DRS.